Building a resilient city for whom? Learning from street vendors' gendered responses to urbanisation in Hanoi. - Kawarazuka, Nozomi (International Institute for Environment and Development, 2016)
This study explores the different ways in which male and female street vendors respond to change and how their responses shape current informal food systems in Hanoi. The approach of this study facilitates an exploration of individual adaptability built upon the institutions of family and village through gendered interdependent relationships.